Distribution and genetic variation of Amblyomma triste (Acari: Ixodidae) in Argentina - Guglielmone, Alberto (2013)
A study was conducted to investigate the distribution of Amblyomma triste in Argentina under the hypothesis that this tick prevails in riparian localities along the Paraná River and adjacent humid environments from 34°30′ S to 25°20′ S, approximately. Ticks were collected from mammals and vegetation in those environments from November 2008 to October 2012. Additionally, genetic variation was tested from Argentinean, Brazilian, Chilean, and Uruguayan populations of A. triste by comparing sequences of 16S rDNA mitochondrial gene. The hypothesis was not confirmed because A. triste were collected at 36°16′ S, well beyond the southern limit predicted, and the distribution along the banks of the Paraná River was not continuous. The northernmost population of A. triste within Argentina was found at 25°42′ S. Still undetermined abiotic factors and plant communities may play a role in modulating the abundance of A. triste because host availability does not appear to be a restriction factor. The genetic variation among A. triste populations from Argentina, Brazil, and Uruguay indicates that they belong to a unique taxon that is considered bona fide A. triste (type locality Montevideo, Uruguay) while it is unclear if the Chilean population of A. triste is conspecific with the other populations investigated in this study. It would be of importance to compare those genetically homogeneous populations with other populations of alleged A. triste, especially populations established in the Nearctic Zoogeographic Region in Mexico and USA.